EFEK KONSERVATISME AKUNTANSI, LEVERAGE, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP EARNING RESPONSE COEFFICIENT - Ahmad, Ruslan (Jurnal Unicorn ADPERTISI, 2024)
The purpose of this study is to find out how accounting conservatism, leverage, firm size and profitability affect the earnings response coefficient. Descriptive study with a quantitative approach is the research methodology used. Multiple linear regression is the data analysis approach used. The population of this study is consumer goods manufacturing companies listed on the Indonesian stock exchange 2018-2020, 78 financial reports from 26 companies are the research sample. Based on the findings from testing the hypothesis of this study, accounting conservatism, leverage, firm size and profitability have a positive effect on the earnings response coefficient. The dependent variable of employee performance can be explained by the independent variable 41.8%, the magnitude of the earning response coefficient is influenced by the variables of accounting conservatism, leverage, firm size and profitability. While 58.2% of the earnings response coefficient is influenced by variables outside the research conducted.